2014
DOI: 10.1002/bip.22489
|View full text |Cite
|
Sign up to set email alerts
|

CH–π interaction in VQIVYK sequence elucidated by NMR spectroscopy is essential for PHF formation of tau

Abstract: One of the histopathological features of Alzheimer's disease (AD) is higher order neurofibrillary tangles formed by abnormally aggregated tau protein. Investigation of the mechanism of tau aggregation is important for the clarifying the cause of AD and the development of therapeutic drugs. The microtubule-binding domain, which consists of repeats of similar amino acids (R1-R4) is thought to form the core component of paired helical filament (PHF). The hexapeptide(306) VQIVYK(311) of R3 has been shown to take a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 29 publications
(39 reference statements)
2
26
0
Order By: Relevance
“…Changes in aromatic amino acid environment during aggregation may be due to CH-π interactions or π-π stacking. [53][54][55] Importantly, the PCA scores plot and loadings for data on dried samples (figures 3C and D respectively) show a very similar pattern as for BSA species in solution and only small frequency shifts are observed in the Amide I, Amide III and skeletal regions, as well as for tyrosine and phenylalanine (listed in supplementary table 2). Together, this suggests that despite the increase in nonregular structure determined by Amide I deconvolution, aggregation species can still be distinguished by the same spectral features irrespective of whether the spectra are measured in wet or dry conditions.…”
Section: Bovine Serum Albumin (Bsa)mentioning
confidence: 65%
“…Changes in aromatic amino acid environment during aggregation may be due to CH-π interactions or π-π stacking. [53][54][55] Importantly, the PCA scores plot and loadings for data on dried samples (figures 3C and D respectively) show a very similar pattern as for BSA species in solution and only small frequency shifts are observed in the Amide I, Amide III and skeletal regions, as well as for tyrosine and phenylalanine (listed in supplementary table 2). Together, this suggests that despite the increase in nonregular structure determined by Amide I deconvolution, aggregation species can still be distinguished by the same spectral features irrespective of whether the spectra are measured in wet or dry conditions.…”
Section: Bovine Serum Albumin (Bsa)mentioning
confidence: 65%
“…Interestingly, despite the prominent position of Tyr-310 within the aggregation-prone hexapeptide PHF6 (amino acids 306 -311), only a handful of studies have specifically investigated the roles of this residue in regulating Tau structure, aggregation, and toxicity. Importantly, none of the previous studies (30,(35)(36)(37)(38)(39)(40)(41)(42) specifically investigated the effects of Tyr-310 phosphorylation in the context of the full-length Tau protein, relying instead on the short PHF6-containing peptides, featuring PHF6-derived sequences as short as three amino acids (43). Santa-Maria et al (44) showed that phosphorylation of Tyr-310 abolished the aggregation of the PHF6 fragment (amino acids 306 -311) in vitro.…”
mentioning
confidence: 99%
“…It follows that the repeat structure of the amyloidogenic MTB domain, marked by subtle differences in the electronic configuration of the repeat segments of the main chain, is likely to be one source of the observed diversity of tau-fibril morphology. The differences in conformational propensities and aggregation properties of the four repeats of the MTB domain of tau attracted considerable attention (Perez et al, 1996, 2007; von Bergen et al, 2000; Tokimasa et al, 2005; Naruto et al, 2010; Sogawa et al, 2012, 2014; Lathuillière et al, 2017; Macdonald et al, 2019). To gauge whether and how these differences are indeed related to the differences in backbone polarization, the folding potential FP i is plotted against its “slope” Δ FP i − 1 → i + 1 separately for each repeat, see the FP i vs. Δ FP i − 1 → i + 1 plots in Figure 4, where the side chains of the histidine residues of MTBD are either neutral (the side chain's imidazole ring is not protonated and σ His = −0.2917, Table 1), Figure 4A, or cationic (the side chain's imidazole ring is protonated and σ His+ = 0.2584, Table 1), Figure 4B.…”
Section: Resultsmentioning
confidence: 99%